The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3762/bjnano.11.96
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale synthesis of splat-shaped Ag–TiO2 nanocomposites for enhanced antimicrobial properties

Abstract: The control over contagious diseases caused by pathogenic organisms has become a serious health issue. The extensive usage of antibiotics has led to the development of multidrug-resistant bacterial strains. In this regard, metal-oxide-based antibacterial nanomaterials have received potential research interest due to the efficient prevention of microorganism growth. In this study, splat-shaped Ag–TiO2 nanocomposites (NCs) were synthesized on the gram scale and the enhanced antibacterial properties of TiO2 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Deshmukh et al (2018) obtained similar results by confirming the antimicrobial activity of TiO 2 with incorporated Ag NPs. Jaber et al (2020) found that Ag/TiO 2 nanoparticles exhibited promising and superior antibacterial properties compared with TiO 2 nanospheres, as confirmed by the bacterial growth and inhibition zone. Desiati et al (2019) concluded that the capability of TiO 2 /Ag NPs to kill bacteria depends on their structure and morphology, which are affected by their calcination temperature.…”
Section: Tio2 Nps and Their Modificationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Deshmukh et al (2018) obtained similar results by confirming the antimicrobial activity of TiO 2 with incorporated Ag NPs. Jaber et al (2020) found that Ag/TiO 2 nanoparticles exhibited promising and superior antibacterial properties compared with TiO 2 nanospheres, as confirmed by the bacterial growth and inhibition zone. Desiati et al (2019) concluded that the capability of TiO 2 /Ag NPs to kill bacteria depends on their structure and morphology, which are affected by their calcination temperature.…”
Section: Tio2 Nps and Their Modificationsmentioning
confidence: 96%
“…Studies investigating antimicrobial activity of TiO 2 NPs using disk diffusion method. References: [1] (Niranjan et al, 2019); [2] (Jaber et al, 2020); [3] (Pavlova et al, 2020); [4] (Saleh et al, 2019). …”
Section: Recent Antimicrobial Analysis Of Tio2 Nanomaterialsmentioning
confidence: 99%
“…The complex of titanium dioxide and silver nanoparticles have low toxicity to human cells and great antibacterial properties 22–24 . Jaber M et al prepared TiO 2 /Ag nanomaterials, and their experimental results demonstrated high biocompatibility and preferable antibacterial activity compared to TiO 2 nanospheres 25 …”
Section: Introductionmentioning
confidence: 99%
“…22-24 Jaber M et al prepared TiO 2 /Ag nanomaterials, and their experimental results demonstrated high biocompatibility and preferable antibacterial activity compared to TiO 2 nanospheres. 25 Polyamino acids (PAAs) are organic compounds that are structurally similar to natural proteins. PAAs exhibit good biocompatibility, and their degradation products are oligopeptides or small amino acid molecules, which are close to neutral and non-toxic.…”
mentioning
confidence: 99%